2002
DOI: 10.1243/09544050260174184
|View full text |Cite
|
Sign up to set email alerts
|

Layer-based machining: Recent development and support structure design

Abstract: There is growing interest in additive and subtractive shaping theories that are synthesized to integrate the layered manufacturing process and material removal process. Recently, layer-based machining has emerged as a promising method for integrated additive and subtractive shaping theory. In this paper, major layer-based machining systems are reviewed and compared according to characteristics of stock layers, numerical control machining con®gurations, stacking operations, input format and raw materials. Suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…AM has the ability to manufacture very complicated 3D physical geometries devoid of geometric restrictions. 1 AM can be classified into Selective Laser Sintering (SLS) also known as Powder Based Additive Manufacturing (PBAM) and Wire and Arc Additive Manufacturing (WAAM), which is Wire Based Additive Manufacturing. 2 WAAM is an aspect of additive manufacturing in which metallic components are manufactured by welding beads in a layer-by-layer manner.…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…AM has the ability to manufacture very complicated 3D physical geometries devoid of geometric restrictions. 1 AM can be classified into Selective Laser Sintering (SLS) also known as Powder Based Additive Manufacturing (PBAM) and Wire and Arc Additive Manufacturing (WAAM), which is Wire Based Additive Manufacturing. 2 WAAM is an aspect of additive manufacturing in which metallic components are manufactured by welding beads in a layer-by-layer manner.…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
“…4 Nevertheless, the surface of WAAM parts has a significant surface roughness in contrast to general Numerical Control (NC) machined parts owing to the WAAM process itself. 5 Researches 2,3,7,14 have investigated into the various aspects of manufacturing using Additive Manufacturing but little research has been done on the machining aspect of it. As part of the study on machining of Additive Manufacturing, Yang et al, 1 concluded that owing to the dynamic effect, Layer Based Machining (LBM) could be better used in large objects devoid of thin walls.…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the magnetic field actually drives the fluid but the field does not directly work on the workpiece. Similarly, using robot(s) to hold milling cutter(s) in the machining operations (Chen and Song, 2001;Yang et al, 2002) is not considered as a hybrid process. In addition, water-jet guided laser cutting (Li et al, 2003;Kray et al, 2007), where the water-jet guides the laser beam before the beam reaches the workpiece surface, is not categorised as a hybrid process, as the jet itself does not change the microstructure of the workpiece or remove the material.…”
Section: Definition Of Hybrid Processesmentioning
confidence: 99%
“…Tengleder and Vergeest (4,5) were early to implement robotic arms for this purpose. Also, Chen (6,7) implemented a robotic system for sculptured surface cutting and later developed a technique that uses layer-based machining to sculpt prototypes made of polymers. In the precious research (8)(9)(10)(11)(12)(13) , a surface sculpturing system based on multi-DOF robot and shaping the 3D work-piece by heated cutting tools is proposed.…”
Section: Introductionmentioning
confidence: 99%